“El Habeas Corpus como mecanismo de protección, en casos de tortura y tratos inhumanos en los Centros de privación de libertad en el Ecuador”. - Freire Andocilla, Pablo Andrés (2023)
In the present research work, an analysis of the institution of Habeas Corpus and its guaranteeing practice of constitutional rights is carried out, being not only an instrument to protect freedom, but also the life and integrity of people, in addition to torture. and inhuman, cruel and degrading treatment, and how these soften the rights to life and integrity of individuals, considering that the State is the executor of this type of constitutional violations. An analysis of Treaties and Conventions that refer to the institution of Habeas Corpus and the obligation of States to guarantee the full enjoyment of the constitutional rights of their citizens is carried out, with emphasis on the protection of the rights to liberty, life and personal integrity. Finally, the application of Habeas Corpus in Ecuadorian legislation is analyzed.